Deteksi Gen TIMP-2 pada Karsinoma Sel Skuamosa Lidah dari Spesimen Blok Parafin - Anshorie, Muhammad Rama; ., Pradipto subiyantoro; Nirmala, Vita (Nexus Biomedika, 2014)
Background : Tongue cancer is the most common intraoral site of cancer occurs throughout the world. When it is diagnosed at early stages of development, the tongue cancer has 80 to 90 % survival rate. Although it has a high survival rate, most patients were diagnosed at a late stage. The purpose of this study was to detect the gene as an inhibitor of cancer cell metastasis factor in a paraffin block sample. Method : This research utilized DNA isolated from 14 parafin blocks which served as samples. First, the DNA were amplified using PCR with appropiate primer. Then electrophoresis were performed to detect the presence of TIMP-2 gene in all of samples. Result : TIMP-2 gene was not detected in all of 14 samples. Summary : This research showed that TIMP-2 gene was not found on agarose gel, indicating that TIMP-2 gene was not present in all of the samples.Â